OEFA: Environmental responsibility, environmental damage and other criteria when decidingsanctioning administrative procedures - Salazar Niño, Elvis (2016)
The following work seeks to review some of the criteria for interpretation of the Environmental Enforcement Tribunal of the OEFA- Organismo de Evaluación y Fiscalización Ambiental, with respect to environmental responsibility, environmental damage, testing and others aspects that holders of mining titles face in the sanctioning  administrative  procedures for which this authority is responsible. The paper also considers that these criteria are not confined to the administrative authority, but are reviewed by the judicial system, and are used to determine legal actions and specialized hearings concerning environmental issues.